2020
DOI: 10.1055/a-1183-3009
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Curricula of Student Education in Europe: Summary of the Experience

Abstract: Background Despite the increasing role of ultrasound, structured ultrasound teaching is only slowly being integrated into the curricula of medical schools and universities all over Europe. Aim To survey the current situation at European universities regarding the integration of ultrasound in student medical education and to report on models of student ultrasound training from selected European universities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 41 publications
0
38
0
3
Order By: Relevance
“…[20] And in European medical schools, a 2016 survey showed that practical skills of US were taught in 56% of undergraduate medical universities; however, the mean number of hours of US instruction was only seven. [16] The same survey indicated lack of funding as one of the primary obstacles to advancing existing programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20] And in European medical schools, a 2016 survey showed that practical skills of US were taught in 56% of undergraduate medical universities; however, the mean number of hours of US instruction was only seven. [16] The same survey indicated lack of funding as one of the primary obstacles to advancing existing programs.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the contemporary state of US education in Switzerland, [16] the University of Basel provided an environment of medical students with minimal to no previous US instruction. This allowed for a neutral assessment of the two different US modalities in medical students at varying stages of their education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In undergraduate medical education, hands-on training of basic ultrasound skills such i. e. knobology as well as interpretation of images with focus on anatomy and structure definition, has been incorporated into the medical school curriculum [9][10][11]. However, a recent survey to explore the inclusion of ultrasound training in student medical education reported that despite the increasing use of ultrasound, its integration is slow with only a minority of the European universities surveyed integrating this program into the pre-clinical curricula [12]. This remains true in postgraduate radiology education.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…B. die "Knopfologie" sowie die Interpretation von Bildern mit Schwerpunkt auf Anatomie und Definition von Strukturen, in das Curriculum der medizinischen Fakultäten aufgenommen [9][10][11]. Eine kürzlich durchgeführte Umfrage zur Einbeziehung des Ultraschalltrainings in die studentische medizinische Ausbildung zeigte, dass die Integration der Sonografie trotz zunehmender Anwendung nur langsam erfolgt und nur sehr wenige der befragten europäischen Universitäten ein solches Programm in das vorklinische Curriculum eingebaut haben [12].…”
Section: Wo Stehen Wir?unclassified